2010
DOI: 10.1177/0956797610382120
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for the Role of Inhibition in Resolving Interference in Memory

Abstract: Interference from competing material at retrieval is a major cause of memory failure. We tested the hypothesis that such interference can be overcome by suppressing competing responses. In a three-phase task, participants in the critical interference condition first performed a vowel-counting task (Phase 1) that included pairs of orthographically similar words (e.g., allergy and analogy). After a delay, participants were asked to solve word fragments (e.g., a _ l _ _ gy) that resembled both words in a pair the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 30 publications
8
75
0
Order By: Relevance
“…There is now ample evidence to suggest that successful memory retrieval involves inhibition of competing concepts in memory, rendering those concepts less active or accessible (e.g., Anderson, Bjork, & Bjork, 1994; Aslan & Bäuml, 2011; Healey, Campbell, Hasher, & Ossher, 2010; for a review, see Storm & Levy, 2012). For instance, in retrieval induced forgetting (RIF) paradigms, participants learn a list of category-exemplar pairs (e.g., FRUIT-apple), followed by a retrieval-practice phase during which some of the studied items are retrieved in response to partial cues (e.g., FRUIT-a____).…”
Section: Introductionmentioning
confidence: 99%
“…There is now ample evidence to suggest that successful memory retrieval involves inhibition of competing concepts in memory, rendering those concepts less active or accessible (e.g., Anderson, Bjork, & Bjork, 1994; Aslan & Bäuml, 2011; Healey, Campbell, Hasher, & Ossher, 2010; for a review, see Storm & Levy, 2012). For instance, in retrieval induced forgetting (RIF) paradigms, participants learn a list of category-exemplar pairs (e.g., FRUIT-apple), followed by a retrieval-practice phase during which some of the studied items are retrieved in response to partial cues (e.g., FRUIT-a____).…”
Section: Introductionmentioning
confidence: 99%
“…In the baseline condition, participants merely read the words of Phase 3 with no prior exposure to them. Evidence of suppression by young adults was reported in Healey et al and can be seen in Figure 2: By contrast with the two control conditions (no-resolution and no-confiict), both of which showed priming of the competitor relative to baseline (Healey et al, 2010), words in the interference condition showed no priming. For young adults, resolving interference entailed suppressing the accessibility of the competitor words to a pre-exposure baseline.…”
mentioning
confidence: 70%
“…Note. For comparison purposes with Healey et al (2010), we excluded any participants who were aware of connections between the phases. In a second step we excluded any participants with too few valid trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, effects similar to retrieval-induced forgetting have been observed in almost any situation in which someone must attempt to retrieve or generate some specific subset of information while not retrieving or generating other information (e.g., Bäuml, 2002;Johnson & Anderson, 2004;Healey, Campbell, Hasher, & Ossher, 2010;Levy, McVeigh, Marful, & Anderson, 2007;Storm, Angello, & Bjork, 2011;Storm, Bjork, Bjork, & Nestojko, 2006;Storm & Patel, 2014).…”
Section: Retrieval-induced Forgettingmentioning
confidence: 99%